The application of the neo-pi-r in - Teferi, Tesfay (My University, 2006)
The five-factor model (FFM) of personality has established itself as the predominant model of personality trait structure (Digman, 1990). The NEO-PI-R has been used as one of the most useful FFM measures. Its reliability and validity has been approved through out the world and this study sought to explore the utility of the NEO-PI-R in the Eritrean context as well by translating the NEO-PI-R English version into Tigrigna language. Reliability and validity analyses were considered and an effort was also made to establish Eritrean norms. The descriptive statistics, norms and reliability co-efficients obtained in this study were not exactly similar to the USA sample, and this was not surprising having cultural difference, however, it was quite satisfactory as a pioneer study in Eritrean context. The scree plot showed that five factors could be extracted in this study. These findings lend support to an extent to the cross-cultural applicability of the instrument. In addition evidence of face, and content validity explorations indicated that this instrument was valid across cultures. Further evidence from inter-group comparisons across variables like age, gender, and level of education supports this argument. However, since the sample size and composition were problematic, there was question in the norming. As a whole the study suggested that NEO-PI-R could make a contribution in the Eritrean context as an initial personality assessment instrument.
Faculty of Humanities. School of Humanities and Communitiy Development. 0214946y tespsuch@yahoo.com
Keywords: Neuroticism; Extravcision; Openness to Experience; Personality; Inventory